Optimization of a sensitive and reliable UPLC-MS/MS method to simultaneously quantify almonertinib and HAS-719 and its application to study the interaction with nicardipine - Dongxin Chen; Jie Chen; Yuxin Shen; Xiaohai Chen; Hailun Xia; Ya-nan Liu; Ren-ai Xu (Taylor & Francis Group, 2024)
Context Almonertinib is primarily metabolized by CYP3A4, so it could interact with a variety of drugs metabolized by CYP3A4, leading to the changes of systemic exposure.Objective For the purpose of this experiment, an ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) assay with accuracy and simplicity was optimized and fully validated for the simultaneous quantitative determination of almonertinib and its metabolite HAS-719, and drug-drug interactions (DDI) between almonertinib and nicardipine in vivo and in vitro was researched.Materials and methods Detection of analytes was achieved by UPLC-MS/MS coupled with multiple reaction monitoring (MRM) in the positive ion mode with ion transitions of m/z 526.01 → 72.04 for almonertinib, m/z 512.18 → 455.08 for HAS-719 and m/z 447.16 → 128.11 for IS, respectively.Results There was favourable linearity in the 0.5-200 ng/mL calibration range for almonertinib and 0.5-100 ng/mL for HAS-719. The lower limit of quantification (LLOQ) for both analytes was 0.5 ng/mL. The precision, accuracy, stability, matrix effect and extraction recovery required for methodological validation were consistent with the requirements of FDA guideline. Then, the UPLC-MS/MS assay was employed successfully on the interactions of almonertinib and nicardipine in vivo and in vitro. The half-maximal inhibitory concentration (IC50) was 1.19 μM in rat liver microsomes (RLM), where nicardipine inhibited the metabolism of almonertinib with a mixed inhibitory mechanism. In pharmacokinetic experiments of rats, it was observed that nicardipine could significantly alter the pharmacokinetic profiles of almonertinib, including AUC(0-∞), AUC(0-t) and Cmax, but had no effect on the metabolism of HAS-719.Conclusion According to the findings, it was indicated that nicardipine could inhibit the metabolism of almonertinib in vitro and in vivo.